2022
DOI: 10.3389/fphar.2022.871481
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Guizhi Wuwu Decoction Improves Arthritis and Pathological Damage of Heart and Lung in TNF-Tg Mice

Abstract: Background: Huangqi Guizhi Wuwu Decoction (HGWD) is a traditional and effective Chinese medicine compound decoction for the treatment of rheumatoid arthritis (RA). However, there is few research on the treatment of rheumatoid cardiopulmonary complications. The present study was to study whether HGWD can alleviate the pathological changes caused by rheumatoid arthritis and cardiopulmonary complications.Methods: Five 3-month-old TNF-Tg mice were treated with HGWD (9.1 g/kg) once a day or the same dose of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…According to numerous studies [ 84 88 ], the progression of these diseases is closely associated with macrophage polarization. According to studies, HQGZWWD may improve rheumatoid arthritis and atherosclerosis by improving the level of inflammation [ 89 – 91 ], but it remains to be determined whether it can exert an anti-inflammatory effect by regulating macrophage polarization. Currently, there is no research on HQGZWWD in the treatment of insulin resistance, asthma, or Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…According to numerous studies [ 84 88 ], the progression of these diseases is closely associated with macrophage polarization. According to studies, HQGZWWD may improve rheumatoid arthritis and atherosclerosis by improving the level of inflammation [ 89 – 91 ], but it remains to be determined whether it can exert an anti-inflammatory effect by regulating macrophage polarization. Currently, there is no research on HQGZWWD in the treatment of insulin resistance, asthma, or Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine has unique advantages in the prevention and treatment of stroke, which has the characteristics of multi-target and multi-pathway synergism, and has become a part of the clinical treatment of stroke in China. Modern pharmacology studies (Lv et al, 2021; Y. Wang et al, 2022); Li et al, 2006) found that HGWD on anti-inflammation, analgesia, anti-oxidation, regulating immune function, improving microcirculation, and blood rheology properties play an essential role in such aspects.…”
Section: Discussionmentioning
confidence: 99%
“…TNFtransgenic (TNF-Tg) mice express the human TNF-α gene on a C57BL/6 background and spontaneously develop erosive polyarthritis with several characteristics observed in patients with RA, as well as the pathological phenotypes of cardiopulmonary complications [25] . Female TNF-Tg mice are useful tools for dissecting the molecular mechanisms of the pathogenic process and evaluating the efficacy of novel therapeutic strategies for RA [26][27][28] and the cardiopulmonary complications of RA [29][30][31] . In the present study, we used TNF-Tg mice to evaluate the protective effect of DGNTT against the cardiopulmonary complications of RA.…”
Section: Introductionmentioning
confidence: 99%